ASEAN financial literacy journey: a bibliometric analysis - Chong, Kok Fei; Khoong, Tai Wai; Wee, Chu Kok; Kusuma, Kumara Adji; Lin, Kok Leong (Malaysian Financial Planning Council, 2024)
Enhancing financial literacy is crucial for empowering individuals by equipping them with the knowledge and skills needed to enhance their financial well-being. Proficiency in making prudent financial choices is crucial for daily existence, allowing to meet both immediate and long-term financial requirements. The objective of this study is to compare bibliometric analysis Scopus bibliographic data indexed articles of ‘financial literacy’ term, for ASEAN countries. This study analysis utilized VOSviewer software to examine the distribution of bibliometric maps. The data filtering process is conducted for "financial literacy" terms contained in the title, keyword, and abstract areas. The papers published from 1989 to 2023 were selected to illustrate the development of financial literacy, and a total of 810 articles attained. Within the thirty decades, the articles showed an increasing trend, which accelerated after 2015. The top five keywords by highest occurrences involved financial literacy, financial behavior, financial, human, and Indonesia. The dataset of 166 items further categorized into five clusters. The ASEAN countries supported SDG2030 financial inclusion initiative, which is associated with FinTech, digital financial literacy, financial services, banking, financial banking, and financial planning terms. The integration of financial literacy within ASEAN countries showed variability patterns. Malaysia illustrated the most diverse study, while Indonesia focused on inclusion, SME, and digitalisation. Singapore, Thailand, Philippines, Cambodia, and Vietnam focus on human aspects. Future study can focus on the integration with adoption of technology. This study serves as a valuable resource for further exploration of financial literacy within ASEAN countries.